Integrating network pharmacology and experimental verification to reveal the anti-inflammatory ingredients and molecular mechanism of pycnogenol - Liu, Hongyu; Shi, Jie; Liu, Fei; Zhang, Litao (Frontiers in Pharmacology, 2024)
Pycnogenol (PYC), a standardized extract from French maritime pine, has traditionally been used to treat inflammation. However, its primary active components and their mechanisms of action have not yet been determined. Therefore, this study employed UPLC-MS/MS (Ultra-high performance liquid chromatography-tandem mass spectrometry) and network pharmacology to identify the potential active components of PYC and elucidate their anti-inflammatory mechanisms. A total of 768 compounds were identified in PYC. Subsequently, 19 anti-inflammatory compounds targeting 85 proteins directly involved in inflammation pathways were identified using InflamNat (Inflammatory Natural Products Database and Predictor) and TCMSP (Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform) databases. PPI (protein-protein interaction) analysis identified IL6, TNF, MMP9, IL1B, AKT1, IFNG, CXCL8, NFKB1, CCL2, IL10, and PTGS2 as core targets. KEGG (Kyoto Encyclopedia of Genes and Genomes) enrichment analysis suggested that the compound in PYC might exert anti-inflammatory effects through the IL17 and TNF signal pathways. Further experiments determined that PYC treatment can reduce the expression of IL6 and IL1β to relieve inflammation in LPS (lipopolysaccharide)induced BV2 cells. Overall, PYC could affect inflammation via multi-components,targets, and -mechanisms. This study provides substantial evidence supporting further research into developing anti-inflammatory treatments.